Application of artificial intelligence in modern public administration: new opportunities and challenges - Shvets, Kateryna; Onyshchenko, Andrii; Kudin, Volodymyr; Korchak, Nataliia; Ivanii, Olena (International Journal of Informatics and Communication Technology (IJ-ICT), 2024)
Humanity is entering a technological era of convergence of artificial intelligence (AI), cyber and biotechnology, robotics and additive manufacturing, which creates unprecedented opportunities and risks on a global scale. AI has quickly become an important topic for global development. Not only the corporate sector but also governments are interested in creating a favourable environment for these technologies. This article explores the role and impact of AI in the context of modern public administration. The authors assess how AI opens up new opportunities for improving public services and the efficiency of management processes. Particular emphasis is placed on the ability of AI to analyse large amounts of data to inform decision-making, improve interaction with citizens, and optimise internal management processes. Potential challenges are also discussed, including ethical issues, privacy concerns, and automation risks. The article proposes strategies for a balanced implementation of AI in public administration, with a special emphasis on the need to develop skills and competencies among civil servants to use these technologies effectively.